OPTIMASI FORMULA MATRIKS PATCH TRANSDERMAL EKSTRAK BIJI MAHONI (Swietenia Mahagoni L.) MENGGUNAKAN SIMPLEX LATTICE DESIGN - Nurista Dida Ayuningtyas; Felisia Bani (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
Background: Mahogany seed extract has been widely studied to overcome blood sugar levels in mice in 50 mg / KgBB. The effectiveness of mahogany seed extracts in reducing sugar levels can be used in transdermal patch matrix preparations. Objective: This study is to manufacture preparations of mahogany seed transdermal matrix patches. Method: create a transdermal patch matrix created by optimizing PVA, HPMC, and PVP with the Design Expert version 10 software using the Simplex Lattice Design method. Evaluation formulas include visual index, thickness (cm), net weight (%), shrinkage drying (%), and drug content (%). Results: completion of the Expert Tool version 10 design analysis obtained 14 run. Each formula is optimized and obtained 13-16 visual values, thickness of 0.1007-0.1030 cm, weight of 0.1415-1461 grams, shrinkage of 9.28-15.25%, content medication 60, 28-94.44%. ANOVA analysis produces significant numbers between averages on visual measurements and weights, formulas for optimal determination. The results of the optimal formula formula obtained by the formula PVA: HPMC: PVP with a concentration of 4.92: 1.02: 0.55% and the desire value 0.829. The results of the validation test using the openstat software t test obtained the equation obtained is valid with p value of 0.787 (p 0.05).Keywords: Mahogany seeds, patches, optimization, simplex lattice design